USING PARS STRATEGY TO IMPROVE SECONDARY SCHOOL STUDENTS’ READING COMPREHENSION - Bella Anggraini (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
Reading holds an important role in our lives. Reading allows us to expand our insight and knowledge. This research highlights the implementation of PARS strategy to improve secondary students’ reading comprehension. The objectives of the research were to find out whether or not there was any significant improvement on students’ reading comprehension of recount text by using PARS strategy and to find out whether or not there was any significant difference in students’ reading comprehension of recount text between those who were taught by using PARS strategy and those who were not. The population of this research was the tenth grade students of SMA 11 Palembang. The sample was taken by using purposive sampling and consisted of 85 students. The method of this research was a quantitative research with quasi experimental research design. The process of collecting the data was done by administering reading comprehension test with multiple choice form. The obtained data were analyzed by running Paired Sample T-test and Independent Sample T-test via SPSS. The result of Paired Sample T-Test revealed that PARS strategy could significantly improve students’ reading comprehension of recount text. Meanwhile, the result of independent sample t-test signified that there was no significant difference in students’ reading comprehension between those who were taught by using PARS strategy and those who were not.